Prevalence of Hemoglobin Mutations and Hemoglobinopathies in Masjed Soleiman County, Southeastern Iran - Fatemeh Asadi (Medical Laboratory Journal, 2019)
ABSTRACT Background and Objectives: Hemoglobinopathies are characterized by defects in the synthesis of globin chains of hemoglobin (Hb). The purpose of the present study was to evaluate mutations associated with thalassemia and other hemoglobinopathies in Masjed Soleiman County, Iran. Methods: This descriptive study was carried out on 456 individuals suspected of having hemoglobinopathies who were referred to health centers of the Masjed Soleiman Country in 2015-2017. Blood samples were collected in EDTA tubes. Complete blood count test was performed and red blood cell indices were determined. Level of Hb variants was measured using capillary electrophoresis. Reverse dot-blot, gap-polymerase chain reaction and Sanger sequencing were carried out to detect mutations. Results: We found that 17.7% of the subjects were heterozygous for β-thalassemia. Frequency of mutations 36/37 (–T), IVS-II-1 (G>A) and IVS-I-110 (G>A) in the β-globin gene was 26.7%, 22% and 16.27%, respectively. In addition, 9.5% of the subjects contained Hb S, Hb D and Hb C, while 1.1% of the subjects showed co-inheritance of an Hb variant and β-thalassemia. In subjects with α-thalassemia, the -α3.7 (57.1%), -- MED–(17.4%), -α4.2 (3.1%) and -α20.5 (1.5%) deletions were found as the most prevalent mutations. Conclusion: In addition to the high prevalence of β-thalassemia and HBB gene mutations, we detected variants Hb S, Hb D, Hb C and co-inheritance of an Hb variants and β-thalassemia in individuals living in the Masjed Soleiman Country. We also identified four mutations in the α-globin gene. These results can be useful for genetic counseling in this population.